Integrating Character Education into Primary School Curriculum - Ahsin, Ahsin; Lesmana, Dody (BADA'A: Jurnal Ilmiah Pendidikan Dasar, 2025)
Character education has become a critical concern in primary education; however, its integration into school curricula remains fragmented across educational contexts. This study aims to systematically synthesize existing research on the integration of character education into primary school curricula. Guided by the PRISMA framework, a systematic literature review was conducted across Scopus, Web of Science, and ERIC, identifying 742 records. After duplicate removal and screening based on predefined inclusion and exclusion criteria, 54 articles were assessed for eligibility, resulting in 32 studies included in the final synthesis. Thematic analysis revealed three dominant themes: (1) curriculum integration models, (2) pedagogical strategies supporting character development, and (3) assessment approaches for character-related outcomes. The findings indicate that effective integration of character education requires coherent alignment between curriculum design, instructional practices, and school culture. This review provides a structured synthesis of current evidence and highlights key methodological and empirical gaps to inform future research and curriculum development in primary education.